2013
DOI: 10.12669/pjms.296.3608
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin resistance in patients with acute coronary events: Risk factors and prevalence as determined by whole blood multiple electrode aggregometry

Abstract: Objectives: To determine the prevalence of aspirin resistance and associated risk factors based on biochemical parameters using whole blood multiple electrode aggregometry. Methods:The study was conducted at the outpatients cardiology clinic of the Universiti Kebangsaan Malaysia Medical Centre (UKMMC) from August 2011 to February 2012. Subjects on aspirin therapy were divided into two groups; first-ever coronary event and recurrent coronary event. Aspirin resistance was measured by a Multiplate® platelet analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Nevertheless, the incidence of ASA nonresponse observed postoperatively in this study was markedly higher than the numbers reported in patients without surgical trauma. 4 In addition to the effects of increased platelet turnover and postoperative hypercoagulability described above, the analgesic medication may have contributed to the high rates in ASA nonresponse. Pyrazolone, as well as other nonsteroidal antiinflammatory drugs, has been shown to interfere with the inhibitory effect of ASA on the synthesis of thromboxane within the normal therapeutic range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the incidence of ASA nonresponse observed postoperatively in this study was markedly higher than the numbers reported in patients without surgical trauma. 4 In addition to the effects of increased platelet turnover and postoperative hypercoagulability described above, the analgesic medication may have contributed to the high rates in ASA nonresponse. Pyrazolone, as well as other nonsteroidal antiinflammatory drugs, has been shown to interfere with the inhibitory effect of ASA on the synthesis of thromboxane within the normal therapeutic range.…”
Section: Discussionmentioning
confidence: 99%
“…2 The influences by genetic predisposition and risk factors, such as diabetes, obesity, or a metabolic syndrome, are under discussion but have not yet been fully clarified. 3,4 Individuals with a reduced response to ASA treatment had an increased risk of cardiovascular or cerebrovascular events such as myocardial infarction or stroke. 2,5,6 A problem addressed by most meta-analyses was the heterogenous definition of ASA nonresponse in the included studies with different technical devices and laboratory analyses used for the detection of ASA nonresponse.…”
Section: Introductionmentioning
confidence: 99%
“…Many past studies have concluded that patients are "aspirin resistant" if they exhibit platelet aggregation using whichever method of aspirin sensitivity testing is available, and many times have not increased the dose of aspirin to see if the patient will become responsive to a higher aspirin dose. 27 Thus, the prevalence of "aspirin resistance" might be grossly overestimated and cause clinicians to avoid the use of aspirin and rely on other currently available antiplatelet agents rather than simply increasing the dose of aspirin. In fact, reports of "aspirin resistance" range from 5.5% to 60%, which could be attributed to many factors including the lack of a good definition or be because many of these studies did not attempt to see if patients were sensitive at higher doses.…”
Section: Discussionmentioning
confidence: 99%
“…Many past studies have concluded that patients are “aspirin resistant” if they exhibit platelet aggregation using whichever method of aspirin sensitivity testing is available, and many times have not increased the dose of aspirin to see if the patient will become responsive to a higher aspirin dose . Thus, the prevalence of “aspirin resistance” might be grossly overestimated and cause clinicians to avoid the use of aspirin and rely on other currently available antiplatelet agents rather than simply increasing the dose of aspirin.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the definition, multiple electrode aggregometry may help in recognizing patients who are low-responders to antiplatelet treatment. Research performed with multiple electrode aggregometry on patients with acute coronary syndrome showed that almost 5% of this group was acetylsalicylic acidresistant while almost 22% did not react to clopidogrel intake [15]. The same studies revealed that a high level of triglycerides is associated with resistance to clopidogrel.…”
Section: Clinical Use Of Mea In Cardiologymentioning
confidence: 95%